Letter to the Editor 34(3) - Bala, Chandra Shekhar; Banik, Gobinda Chandra; Perveen, Shaila (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2016; 34(3): 178-180